Unsteady RANS Modeling of Flow around Two-Dimensional Rectangular Cylinders with Different Side Ratios at Reynolds Number 6.85 × 105. (15th September 2020) - Wang, Shubiao; Cheng, Wenming; Du, Run; Wang, Yupu
Abstract : In practical engineering, the Reynolds number ( Re ) of box girder structure is usually very high ( Re ≥ 10 5 ), while most investigations of the flow around bluff bodies are concentrated on relatively lower Reynolds numbers (i.e., Re = 10 3 –10 4 ). This paper presented a numerical study of the unsteady flow around two-dimensional rectangular cylinders under a Reynolds number of 6.85 × 10 5 with different side ratios ( R = b/h, width to height) ranging from 0.1 to 4.0. Three unsteady Reynolds-averaged Navier-Stokes (RANS) two-equation k-ε turbulence models (standard, RNG, and realizable) were adopted in the study. The realizable k-ε model was chosen because it was found to perform the best among three models in the main aerodynamic integral parameters. According to the distinctions of aerodynamic characteristics with different side ratios, three regimes were divided and discussed in detail. The distribution of surface pressure over cylinders, the wake parameters, and vorticity contours of the rectangular cylinders with different side ratios were discussed.